IDENTIDADE CULTURAL BRASILEIRA PRESENTE NAS REPRESENTAÇÕES DOS CAPOEIRISTAS DO GRUPO MUZENZA - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The aim of this thesis was to analyse the representations of Brazilian cultural identity provided by capoeiristas of the Muzenza Group worldwide. To that end, a qualitative research approach was chosen. Firstly, bibliographical research was performed regarding the issues of memory, social representations, identity, cultural identity and Brazilian national identity. This was followed by a survey of relevant information regarding the history of capoeira and the Muzenza Group. Subsequently, field research was carried out using participant observation and semi-structured interviews as methods that allowed access to empirical data. The interviews were collected during two important events for the Muzenza Group: the "Eighth World Championship of Muzenza Capoeira" and the first “Berimbau Played, I will Play" (a capoeira „baptism‟ and graduation ceremony). In order to analyse the latter, it was decided to use the methodology of content analysis. A total of thirty interviews were conducted, fourteen of which with non-Brazilians, fourteen with Brazilians, and two with Brazilians who taught capoeira classes outside Brazil. It was concluded that capoeira influences the identity formation of its practitioners, since the identity elements of Brazilian culture such as ginga, malandragem and joy are present in the discourse of capoeira practitioners from the Muzenza Group, independently of them being Brazilian or foreigners.
Keywords: Capoeira; Identidade; Identidade cultural brasileira; Grupo Muzenza; Capoeira; Identity; Brazilian cultural identity; Muzenza Group; CNPQ::CIENCIAS SOCIAIS APLICADAS